A review of the measurement of grip strength in clinical and epidemiological studies: towards a standardised approach. - Roberts, H; Denison, H; Martin, H; Patel, H; Syddall, H; Cooper, C; Sayer, A (2011)
BACKGROUND: the European Working Group on Sarcopenia in Older People has developed a clinical definition of sarcopenia based on low muscle mass and reduced muscle function (strength or performance). Grip strength is recommended as a good simple measure of muscle strength when 'measured in standard conditions'. However, standard conditions remain to be defined. METHODS: a literature search was conducted to review articles describing the measurement of grip strength listed in Medline, Web of Science and Cochrane Library databases up to 31 December 2009. RESULTS: there is wide variability in the choice of equipment and protocol for measuring grip strength. The Jamar hand dynamometer is the most widely used instrument with established test-retest, inter-rater and intra-rater reliability. However, there is considerable variation in how it is used and studies often provide insufficient information on the protocol followed making comparisons difficult. There is evidence that variation in approach can affect the values recorded. Furthermore, reported summary measures of grip strength vary widely including maximum or mean value, from one, two or three attempts, with either hand or the dominant hand alone. CONCLUSIONS: there is considerable variation in current methods of assessing grip strength which makes comparison between studies difficult. A standardised method would enable more consistent measurement of grip strength and better assessment of sarcopenia. Our approach is described.